A consistent data set of Antarctic ice sheet topography, cavity geometry, and global bathymetry - Timmermann, R.; Le Brocq, A.; Deen, T.; Domack, E.; Dutrieux, P.; Galton-Fenzi, B.; Hellmer, H.; Humbert, A.; Jansen, D.; Jenkins, Adrian; Lambrecht, A.; Makinson, K.; et al. (Earth System Science Data, 2010)
Sub-ice shelf circulation and freezing/melting rates in ocean general circulation models depend critically on an accurate and consistent representation of cavity geometry. Existing global or pan-Antarctic topography data sets have turned out to contain various inconsistencies and inaccuracies. The goal of this work is to compile independent regional surveys and maps into a global data set. We use the S-2004 global 1-min bathymetry as the backbone and add an improved version of the BEDMAP topography (ALBMAP bedrock topography) for an area that roughly coincides with the Antarctic continental shelf. The position of the merging line is individually chosen in different sectors in order to capture the best of both data sets. High-resolution gridded data for ice shelf topography and cavity geometry of the Amery, Fimbul, Filchner-Ronne, Larsen C and George VI Ice Shelves, and for Pine Island Glacier are carefully merged into the ambient ice and ocean topographies. Multibeam survey data for bathymetry in the former Larsen B cavity and the southeastern Bellingshausen Sea have been obtained from the data centers of Alfred Wegener Institute (AWI), British Antarctic Survey (BAS) and Lamont-Doherty Earth Observatory (LDEO), gridded, and blended into the existing bathymetry map. The resulting global 1-min Refined Topography data set (RTopo-1) contains self-consistent maps for upper and lower ice surface heights, bedrock topography, and surface type (open ocean, grounded ice, floating ice, bare land surface). The data set is available in NetCDF format from the PANGAEA database at doi:10.1594/pangaea.741917.